Análise do risco de fraturas ósseas nas mulheres idosas por meio da ferramenta FRAX - Sousa, Cristina de Jesus (2018)
This is a quantitative, cross-sectional and descriptive study whose general objective was to evaluate the bone quality of elderly women with more than 60 years of age attending a general gynecology clinic in the Distrito Federal, through the application of the FRAX Tool. The study site was a private general gynecological clinic and the sample consisted of 147 were elderly women (60 to 90 years). For the data collection, three instruments were used: a sociodemographic questionnaire, the FRAX tool and the FRAQ-Brazil instrument. Comparisons of proportions between two independent groups were performed using Fisher's exact test. Categorical variables were described with counts and proportions. Quantitative variables of normal and asymmetric distribution were described as mean ± standard deviation and median (interquartile range) respectively. Normality was assessed by visual inspection of histograms. The R software was used in the statistical analysis of data. All probabilities of significance are bilateral and values less than 0.05 are considered statistically significant. The results obtained are found in articles 1 and 2. The research allowed an intense literature review to contribute to an understanding of which factors limit the use of the FRAX Tool, and which groups of older people should be better and more carefully analyzed for orientation. We found a mean and high risk of osteoporotic fractures assessed by applying the FRAX tool in non-elderly patients by 0.3%, in elderly patients up to 79 years old was found in 3,7% and in 45,5% of the elderly women above of 80 years. It can be concluded that the FRAX tool, despite some limitations, is important for the early identification and screening of individuals at risk of fractures due to its simplicity of application, allowing early and safe therapeutic decision making. It was also concluded that there is a significant increase in the risk of osteoporotic fractures with advancing age.